Shopping Decisions for Transactions in Online Stores Based on Product Quality and Price - Reza, Siti Nur; Avianti, Widiya (PT. AHS Konsultan dan Pelatihan, 2024)
This study aims to analyze the influence of product quality and price on Lazada online shop purchase decisions on consumers in Ciawi Wanayasa Village, Purwakarta. The source of data in this study was obtained from a questionnaire (primary) distributed to the respondents. The population of this study is Lazada consumers in Ciawi Village. The sample of this study is 150 people. Quantitative Research Methods by conducting data analysis through SmartPLS were carried out a series of tests, namely descriptive statistics, outer model, inner model structural (R-Square, Q2 Predictive Relevance) and hypothesis testing. The results of this study show that partially, the two independent variables, namely product quality and price, affect the dependent variable, namely the purchase decision. and simultaneously product quality and price affect the purchase decision.